Usefulness of oxygen reserve index (ORi) in clinical practice - Barud, Małgorzata (Medical Studies/Studia Medyczne, 2023)
Oxygen is the most common and widely used drug. Oxygen therapy is used not only among mechanically ventilated patients in intensive care units, but also in the perioperative period and in patients requiring oxygen supplementation in other hospital wards. The main methods of monitoring the blood oxygenation level include arterial blood gases and pulse oximetry. A new parameter that allows the monitoring of patients’ oxygenation status is the oxygen reserve index (ORi). The ORi provides easy, non-invasive, bedside monitoring of oxygen reserve capacity. The oxygen reserve index reflects the partial pressure of oxygen in arterial blood (PaO2) in the range 100–200 mm Hg. It therefore allows the detection of mild hyperoxia, enabling the safe use of lower concentrations of oxygen in the breathing mixture. It is also a useful tool in predicting impending hypoxia. This paper summarizes the usefulness of oxygen reserve index monitoring in various clinical situations in everyday anaesthesiology practice.